Nitensidine A, a guanidine alkaloid from Pterogyne nitens, induces osteoclastic cell death - Tajima, Yasuhiro; Murase, Hayato; Satake, Kazuhiro; Mitani, Yuji; Regasini, Luis Octavio [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Efferth, Thomas; Nakagawa, Hiroshi (Springer Nature, 2013)
Nitensidine A is a guanidine alkaloid isolated from Pterogyne nitens, a common plant in South America. To gain insight into the biological activity of P. nitens-produced compounds, we examined herein their biological effects on osteoclasts, multinucleated giant cells that regulate bone metabolism by resorbing bone. Among four guanidine alkaloids (i.e., galegine, nitensidine A, pterogynidine, and pterogynine), nitensidine A and pterogynine exhibited anti-osteoclastic effects at 10 μM by reducing the number of osteoclasts on the culture plate whereas galegine and pterogynidine did not. The anti-osteoclastic activities of nitensidine A and pterogynine were exerted in a concentration-dependent manner, whereas nitensidine A exhibited an approximate threefold stronger effect than pterogynine (IC50 values: nitensidine A, 0.93 ± 0.024 μM; pterogynine, 2.7 ± 0.40 μM). In the present study, the anti-osteoclastic effects of two synthetic nitensidine A derivatives (nitensidine AT and AU) were also examined to gain insight into the structural features of nitensidine A that exert an anti-osteoclastic effect. The anti-osteoclastic effect of nitensidine A was greatly reduced by substituting the imino nitrogen atom in nitensidine A with sulfur or oxygen. According to the differences in chemical structures and anti-osteoclastic effects of the four guanidine alkaloids and the two synthetic nitensidine A derivatives, it is suggested that the number, binding site, and polymerization degree of isoprenyl moiety in the guanidine alkaloids and the imino nitrogen atom cooperatively contribute to their anti-osteoclastic effects. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Cytotoxicity; Guanidine alkaloids; Osteoclast; Pterogyne nitens; Structure and activity relationship